Genomic insights of the WRKY genes in kenaf (Hibiscus cannabinus L.) reveal that HcWRKY44 improves the plant’s tolerance to the salinity stress - Chen, Meixia; She, Zeyuan; Aslam, Mohammad; Liu, Ting; Wang, Zerong; Qi, Jianmin; Niu, Xiaoping (Frontiers in Plant Science, 2022)
The WRKY transcription factors (TFs) are among the most diverse TF families of plants. They are implicated in various processes related to plant growth and stress response. Kenaf (Hibiscus cannabinus L.), an important fiber crop, has many applications, including the phytoremediation of saline-alkaline soil. However, the roles of WRKY TFs in kenaf are rarely studied. In the present study, 46 kenaf WRKY genes were genome-widely identified and characterized by gene structure, phylogeny and expression pattern analysis. Furthermore, the HcWRKY44 gene was functionally characterized in Arabidopsis under salinity and drought stresses. HcWRKY44 is a nuclear-localized protein that is positively induced by salinity and drought, with roots showing maximum accumulation of its transcripts. Under NaCl and abscisic acid (ABA) stress conditions, plants overexpressing HcWRKY44 had higher germination rates, better root growth and increased survival than control plants; however, it did not improve the ability to withstand drought stress. Moreover, ABA signaling genes (ABI1, ABI2, and ABI5), ABA-responsive genes (ABF4, RD29B, COR15A, COR47, and RD22), stress-related genes (STZ, P5CS, and KIN1), and ionic homeostasis-related genes (SOS1, AHA1, AHA2, and HKT1) were positively induced in HcWRKY44 transgenic plants under NaCl treatment. These results suggest that HcWRKY44 improved plant’s tolerance to salt stress but not osmotic stress through an ABA-mediated pathway. In summary, this study provides provided comprehensive information about HcWRKY genes and revealed that HcWRKY44 is involved in salinity tolerance and ABA signaling.